Recovery of a high-pressure phase formed under laser-driven compression - Gorman, MG; McGonegle, D; Tracy, SJ; Clarke, SM; Bolme, CA; Gleason, AE; Ali, SJ; Hok, S; Greeff, CW; Heighway, PG; Hulpach, K; Glam, B; et al. (American Physical Society, 2020)
The recovery of metastable structures formed at high pressure has been a long-standing goal in the field of condensed matter physics. While laser-driven compression has been used as a method to generate novel structures at high pressure, to date no high-pressure phases have been quenched to ambient conditions. Here we demonstrate, using in situ x-ray diffraction and recovery methods, the successful quench of a high-pressure phase which was formed under laser-driven shock compression. We show that tailoring the pressure release path from a shock-compressed state to eliminate sample spall, and therefore excess heating, increases the recovery yield of the high-pressure ω phase of zirconium from 0% to 48%. Our results have important implications for the quenchability of novel phases of matter demonstrated to occur at extreme pressures using nanosecond laser-driven compression.